KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU HASIL BELAJAR DI SDIT TUNAS HARAPAN ILAHI KOTA TANGERANG - Hidayat Hidayat; Priyo Susilo (Universitas Muhammadiyah Tangerang, 2019)
The objectives of this thesis research are to describe leadership types of SDIT THI headmaster, to describe the obstacles to increase the quality of education, to describe the effort to increase the quality of education, to describe the education quality of SDIT THI Kota Tangerang. Research method applied was descriptive qualitative research. Data collecting obtained from information, place and leadership activity of headmaster and document. Data retrieval technique was in the form of interview, observation, and document study. Data validity test was done by applying source triangulation, method triangulation. Data analysis technique that isa data reduction, data display, and conclusion drawing which is interact each other. Result of research in the form of specific findings that are 1) The increasing of education quality in SDIT THI depends on the headmaster leadership types. The leadership types of SDIT THI headmaster is democratic type. 2) In general, SDIT THI doesn’t have the the significant obstacles to improve the quality of education. 3) Headmaster effort is quite effective to improve the quality of education in SDIT THI. 4) The education quality of SDIT THI is quite good and congruen to standard quality of Jaringan Sekolah Islam Terpadu